A Review On Comparative Analysis Of Different Transport Layer Protocols In MANETs (International Journal of Engineering and Computer Science, 2015)
Mobile Ad-hoc Networks (MANETs) allow wireless nodes to form a network without requiring a fixed framework. Ad hoc network is a network which comprises of nodes that use a wireless interface to send information from source to destination. Since the nodes in a network of this kind can serve as routers and hosts so they can forward packets on part of other nodes and run user applications. The traffic scenario basically defines the reliability and capability of information transmission, which creates its performance analysis.TCP (Transmission Control Protocol), is a standard that defines how to establish and maintain a network conversation via which application programs can exchange data. Stream Control Transmission Protocol (SCTP) is a transport layer protocol which serve same role to the famous protocols Transmission Control Protocol (TCP) and User Datagram Protocol (UDP)